THE INFLUENCE OF ISLAMIC COUNSELING GUIDANCE ON COMMUNITY LEGAL AWARENESS IN KULON PROGO REGENCY - Pahlewi, Reza Mina (Acitya Wisesa: Journal of Multidisciplinary Research, 2024)
Legal awareness is a crucial factor in building an orderly and compliant society. In Kulon Progo Regency, although an Islamic counseling program has been implemented, its influence on community legal awareness remains to be studied. This research aims to measure the influence of Islamic counseling guidance on community legal awareness in Kulon Progo Regency and examine the extent to which the program may influence the current level of legal compliance. This research adopted a quantitative method with a survey approach. The sample consisted of 100 respondents randomly selected among communities in Kulon Progo Regency. Data was collected through a questionnaire that measured the level of legal awareness prior to and upon following the Islamic counseling guidance. Data analysis was conducted using statistical tests to assess significant changes in legal awareness. The research findings revealed a significant increase in the community's legal awareness after participating in the Islamic counseling guidance. The average legal awareness score increased from 62% to 78%, with a p value <0.05 indicating that this change was statistically significant. Islamic counseling guidance has a positive influence on community legal awareness in Kulon Progo Regency. The program is effective in improving legal understanding and compliance among participants. This research recommends that Islamic counseling guidance should be expanded and promoted further to achieve a greater impact within the community.